Ekranisasi Novel pada Film Mariposa Sutradara Fajar Bustomi - Rizki Rahmadi; Dani Manesah (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
The adaptation of a novel into a film, known as ekranisasi, is a challenging process due to the differences between the two mediums, namely literature and visual storytelling. This study examines the ekranisasi process of the novel Mariposa by Luluk Hadiya Fauzia, directed by Fajar Bustomi. The purpose of this research is to analyze the extent to which the Mariposa film retains the core narrative of the novel and how cinematographic elements are used to replace the internal narration found in the literary work. Through a qualitative approach and literature study, the research reveals that, despite significant changes in character development and plot structure, the main themes of teenage love, perseverance, and self-growth are preserved. The film employs cinematographic techniques, such as lighting, color, and shot composition, to more directly depict the emotions and internal conflicts of the main characters. Additionally, symbolism, such as the butterfly representing transformation, strengthens the themes and moral messages conveyed. The findings of this study show that the Mariposa film successfully offers a new experience for the audience and demonstrates that novel-to-film adaptations can succeed, even with changes in storytelling methods, as long as the essence of the literary work is maintained.